Two new species of Centaurea sect. Microlophus (Asteraceae, Cardueae) from Iran - Ranjbar, Massoud; Askari, Ali; Mohammadi, Somayeh (Phytotaxa, 2021)
Centaurea dezfulica and C. kuhdashtensis are described and illustrated as new species. They belong to C. sect. Microlophus and are endemic to NW Iran. Centaurea dezfulica is closely related to C. pabotii but distinguished from the latter species by densely hispid hairs, plant height 45–50 cm, upper cauline leaves decurrent, segments of lower cauline leaves in 7–8 pairs, larger involucres, 20–23 × 10–20 mm, inner phyllaries obtuse, appendage 2–3 mm long, larger spinule (1–2 mm long) and short central florets and achene. Centaurea kuhdashtensis is distinguished from C. koeieana by loosely hispid hairs, larger lower cauline leaves, pinnatipartite-pinnatilobate, or pinnatifid median [lower] cauline leaves, segments of lower cauline leaves in 15–17 pairs, and those of basal cauline leaves in 14–15 pairs. An updated key to C. dezfulica and C. kuhdashtensis and their closely related taxa in Iran is also provided.